Understanding and using English grammar - Azar, Betty Schrampfer, 1941-; Hagen, Stacy A., 1956- (White Plains, N.Y. : Pearson Education, 2009)
The classic text for intermediate through advanced students provides a clear, visual presentation of grammar in terms easily understandable to students. Grammar explanations teach situationally appropriate English, both formal and colloquial and make distinctions between British and American usage. Each presentation is followed by graded activities that promote speaking, listening, and writing skills. --from publisher description
Overview of verb tenses -- Present and past; simple and progressive -- Perfect and perfect progressive tenses -- Future time -- Review of verb tenses -- Subject-verb agreement -- Nouns -- Pronouns -- Modals, part 1 -- Modals, part 2 -- The passive -- Noun clauses -- Adjective clauses -- Gerunds and infinitives, part 1 -- Gerunds and infinitives, part 2 -- Coordinating conjunctions -- Adverb clauses -- Reduction of adverb clauses to modifying adverbial phrases -- Connectives that express cause and effect, contrast, and condition -- conditional sentences and wishes -- Appendix: Supplementary grammar charts. Basic grammar terminology ; Questions ; Contractions ; Negatives ; Preposition combinations ; The subjunctive ; Troublesome verbs
Keywords: English language -- Textbooks for foreign speakers; English language -- Grammar -- Problems, exercises, etc